PCR based detection of HPV 16 and 18 genotypes in normal oral mucosa of tobacco users and non-users. (August 2014) - Pattanshetty, S; Kotrashetti, VS; Nayak, R; Bhat, K; Somannavar, P; Babji, D
Abstract There is increasing evidence of a causal association between human papillomavirus (HPV) and oral squamous cell carcinoma (OSCC). Several studies have shown that HPV is associated with increased risk of oral cancer independent of exposure to tobacco and alcohol. The association is valid for HPVs 16 and 18, which generally are considered high risk types, because they have been detected in oral dysplastic lesions and cancers. We determined the baseline prevalence of HPVs 16 and 18 in normal oral mucosa of individuals with and without tobacco habit. PCR was used for DNA collected by oral smears to detect HPV 16/18 DNA in normal oral mucosa of 60 healthy individuals who were assigned to two groups of 30 subjects each. One group had a tobacco habit, the other did not. The tobacco user group comprised individuals who were tobacco chewers only. Sixty-five percent of individuals were positive for HPV 16/18 DNA, but HPV 16/18 positivity was less in individuals with tobacco habit than in those without tobacco habit. No significant association was found between the presence of HPVs and gender, age or duration of chewing habit, or between groups with and without a tobacco habit. We propose that HPVs16 and 18 commonly are present in normal oral mucosa and emphasize the importance of distinguishing clinical, subclinical and latent HPV infections when investigating HPVs and OSCC.